ระบบการศึกษาทางไกลระดับอุดมศึกษาไทยในทศวรรษหน้า - บุญปริตร นิตยา; ศุภวรรณ สารีพันธุ์; สังข์ศรี สุมาลี; บุญอำไพ ทิพย์เกสร (วารสารวิชาการศึกษาศาสตร์ ศรีนครินทรวิโรฒ, 2018)
บทคัดย่อ การวิจัยนี้มีวัตถุประสงค์ 1) เพื่อศึกษาสภาพเกี่ยวกับระบบการศึกษาทางไกลระดับอุดมศึกษาไทยในปัจจุบัน 2) เพื่อพัฒนาระบบการศึกษาทางไกลระดับอุดมศึกษาไทยในทศวรรษหน้า และ 3) เพื่อประเมินระบบการศึกษาทางไกลระดับอุดมศึกษาไทยในทศวรรษหน้า กลุ่มตัวอย่างประกอบด้วย 1) ผู้บริหาร อาจารย์ และเจ้าหน้าที่ในสถาบันอุดมศึกษาในประเทศไทยที่มีการจัดการเรียนการสอนทางไกล จำนวน 3 แห่งจำนวน 285 คน และ 2) ผู้เชี่ยวชาญด้านการศึกษาทางไกลจำนวน 17 คน เครื่องมือในการรวบรวมข้อมูล คือ แบบสอบถามสำหรับบุคลากรในสถาบันอุดมศึกษาในประเทศไทยที่มีการจัดการเรียนการสอนทางไกล แบบสัมภาษณ์และแบบสอบถามสำหรับผู้เชี่ยวชาญด้านการศึกษาทางไกลตามกระบวนการวิจัยด้วยเทคนิคแบบ EDFR (Ethnographic Delphi Futures Research) วิเคราะห์ข้อมูลโดยการหาค่าความถี่ ค่าร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน ค่ามัธยฐาน ค่าพิสัยระหว่างควอไทล์ และการวิเคราะห์เนื้อหาสำหรับข้อมูลเชิงคุณภาพ ผลการวิจัยในประเด็นสำคัญ คือ 1) บุคลากรในสถาบันอุดมศึกษาในประเทศไทยที่มีการจัดการเรียนการสอนทางไกลมีความคิดเห็นในภาพรวมของสภาพการบริหารจัดการการศึกษาทางไกลในปัจจุบันตามองค์ประกอบทั้ง 9 ด้าน อยู่ในระดับมากที่สุดและระดับมาก เรียงลำดับจากมากไปหาน้อยได้ดังนี้ ด้านอุดมการณ์ ด้านการจัดการเรียนการสอน ด้านการบริหารและการจัดการ ด้านการวัดและประเมินผลของการเรียนการสอนทางไกล ด้านสื่อและเทคโนโลยีการศึกษาทางไกล ด้านผู้สอน ด้านการให้บริการการศึกษาทางไกล ด้านผู้เรียน และด้านหลักสูตร ตามลำดับ 2) การพัฒนาระบบการศึกษาทางไกลระดับอุดมศึกษาไทยในทศวรรษหน้าประกอบด้วย 11 องค์ประกอบ ได้แก่ ด้านอุดมการณ์ การบริหารและการจัดการ หลักสูตร ผู้สอน ผู้เรียน การจัดการเรียนการสอน สื่อและเทคโนโลยีการศึกษาทางไกล การให้บริการช่วยเหลือผู้เรียนในระบบการศึกษาทางไกล การวัดและประเมินผลของการเรียนการสอนทางไกลการประกันคุณภาพ และการวิจัยสำหรับการศึกษาทางไกล และ 3) ผู้เชี่ยวชาญด้านการศึกษาทางไกล ส่วนใหญ่มีความเห็นด้วยในระดับมากที่สุด กับ 11 องค์ประกอบดังกล่าว คำสำคัญ : ระบบการศึกษาทางไกล, อุดมศึกษาไทย ABSTRACT This research aims to study current status of distance education system of the Higher Education institutions in Thailand, to developa distance education system for Thai Higher Education institutions in the next decade, and to evaluate the distance education system for Thai Higher Education institutions in the next decade. Samples who participated in this study can be divided into 2 groups. The first group consists of 285 participants; they were selected from administrative teams, instructors, and general officers who work for 3 Thai higher education institutions where distance education is offered. The second group consists of 17 participants selected from distance education specialists. Data collection instruments were survey questionnaires designed for officers from Thai higher education institutions where distance education is offered. Interviewing questions and survey questionnaires designed for distance education specialists based on the EDFR (Ethnographic Delphi Futures Research) technique. Quantitative data were analyzed using frequency, percentage, mean, standard deviation, median, and interquartile range. Qualitative data were analyzed using content analysis. Research findings are shown significant results. First, the officers who work for Thai higher education where distance education is offered implied that they had very positive and positive attitudes toward overall 9 items regarding distance education administrative and management status at present. The items can be ranked from the highest to the lowest score as follows: Ideology, Teaching method, Administration and management, Distance education evaluation and assessment, Distance education media and technology, Instructors, Distance education service, Learners, and Curriculum respectively. Second, the distance education system for Thai Higher Education institutions in the next decade which was developed consisted of 11 components, namely Ideology, Administrative and management, Curriculum, Instructors, Learners, Instruction, Distance education technology and media, Distance education support for learners, Distance education evaluation and assessment, Quality assurance, and Research on distance education. Third, in general, distance education specialists strongly agreed with such 11 components. Keywords : Distance education system, Thai Higher Education